(untitled) (Global Journal of Science Frontier Research, 2023)
As was Einstein s original idea we suppose that the speed of light is altered in the presence of mass by a change in its dielectric susceptibility Our explanation of the phenomena of quantum mechanics is a continuation of Einstein search for hidden variables Mass induces a curvature in spacetime This has two effects New volume is created and this would mean that there is not exactly a point particle but matters in a way occupies some volume Another result is that spacetime becomes cyclic and quantities like the action are quantized because they depend on angles through which the observer witnesses the events